European slave trading in the Indian Ocean, 1500-1850 - Allen, Richard Blair (Indian Ocean studies series., 2014)
Between 1500 and 1850, European traders shipped hundreds of thousands of African, Indian, Malagasy, and Southeast Asian slaves to ports throughout the Indian Ocean world. The activities of the British, Dutch, French, and Portuguese traders who operated in the Indian Ocean demonstrate that European slave trading was not confined largely to the Atlantic but must now be viewed as a truly global phenomenon. European slave trading and abolitionism in the Indian Ocean also led to the development of an increasingly integrated movement of slave, convict, and indentured labor during the late eighteent.